IMPLANTATION DE « L’ARMEE DU SALUT » EN REPUBLIQUE DEMOCRATIQUE DU CONGO. DE 1934 A 2005. - Travaux Jérôme GEOLOLO BAPOWA (IJRDO - Journal of Social Science and Humanities Research, 2020)
The Salvation Army has been implanted in Democratic Republic of Congo (RDC) October 14, 1934 by the adjutant Léon Henri Becquet of the nationality Belgian; after a mission of prospecting expanded in 1933 insider by the general EDWARD HIGGINS to the Congo Belgian. The work saltiest began in Kinshasa (Léopoldville) before spreading to other provinces of the RDC and to other African countries. The Salvation Army in Congo carries itself in marvel and it is liveliness to continue and to accomplish the work and his/her/its founder’s vision to win the souls to Christ.